Absence of advantageous wagering does not mean that awareness is fully abolished - Szczepanowski, Remigiusz (Consciousness and cognition, 2010)
Post-decision wagering (Persaud, McLeod, & Cowey, 2007) has been proposed as a method of demonstrating that perception can occur without conscious awareness. When wagering is independent from above-chance performance there is evidence of a lack of awareness of the correctness of the first-order discriminations. However, there are reasons to believe that the contingency analysis conducted by Persaud and colleagues failed to measure “the zero accuracy-wagering criterion”. The author shows that a Pearson chi-square test employed by Persaud and colleagues is unable to accommodate the hypothesis of partial independence between accuracy and advantageous wagering. On the contrary, the problem of “the zero accuracy-wagering criterion” is best conducted with log-linear models. Moreover, log-linear analysis suggests that absence of advantageous wagering is not sufficient evidence for a lack of conscious awareness. In the case of the blindsight study, there was compelling evidence that the patient GY was partially aware of having information about the correctness of his decisions.